Response surface methodology for evaluation of blanching effects on antioxidant capacity and physical quality of ground pork product treated with mulberry leaves - Mahidsanan, Thitikorn; Chanthabal, Akkara (Naresuan University Journal: Science and Technology (NUJST); Vol 31 No 1 (2023): January - March 2023, 2022)
Although hot water blanching has an important effect on inactivating microorganisms, the antioxidant capacity of foods might be lost by this process. The purpose of this work was to evaluate the predictive response surface models (RSM) and their mathematical equations for monitoring the quality of ground pork incorporated with mulberry leaves (12.5 g/kg) during blanching. The temperatures and times were modelled to create RSM mathematical equations based on the alteration of each parameter, including pH, texture characteristics, color values (L*, a* and b*), and antioxidant capacity. The results showed that pH values and hardness were affected by the blanching temperature, while the b* was affected by the blanching times. In contrast, the stringiness, and L* and a* were not altered by any blanching factors. Following the antioxidant activity, the percentage of DPPH radical-scavenging activity increased with an increase in all blanching factors. Considering the normal probability plots of each parameter along with the verification of the assumption of ANOVA, these results indicated that their predictive equations could be a prototype of RSM models for predicting the alterable physical quality and antioxidant capacity of ground pork incorporated with mulberry leaves during blanching. Keywords: Response surface model (RSM), Blanching effect, Ground pork product treated with mulberry leaves